Implementation of the Concept of Religious Moderation in Islamic Education: Study the Thought of M. Quraish Shihab - Ahmad Khoiron Nasihin; Ainol Ainol; Ahmad Khumaidi (STAI Syaichona Moh. Cholil Bangkalan, 2023)
Extremes in religion are a serious problem when looking at the country's heterogeneity and multiculturalism level. The results of extremes tend to give birth to religiously labeled conflicts, which require religious moderation to be embodied, one of which is through educational channels. Education is considered a path with potential because it is an educational forum for producing a moderate generation of the nation, one of which is Islamic Religious Education. Learning that is an aspect of education can be used as a path to implement religious moderation. Moreover, this study aims to reveal the concept of religious moderation according to M. Quraish Shihab and its application to learning Islamic religious education. This research uses a qualitative approach with the type of research library research. Data collection techniques are documentation and content analysis as analytical techniques. From this study, several findings were found that religious moderation is a middle position (balance) in religion, meaning that it stands between two opposing sides of the extreme, while the purpose of religious moderation is to create a just, consistent, firm, and balanced perspective on both worldly and ukhrawi affairs. Moreover, religious moderation can be applied through learning methods such as discussions, group work, and tourist work.